Customer Satisfaction As A Bridge: The Impact Of Service Quality And Product Diversification On Loyalty - Nyoman Indra Wiratama; Made Setini; Putu Ngurah Suyatna Yasa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of product diversity and service quality on customer loyalty through customer satisfaction as an intervening variable in PT. Tirta Sakti Mandiri. The food and beverage (F&B) industry is a vital sector in the economy, offering significant market potential amid increasing competition. Customer loyalty is the key to success; However, the data shows a decline in loyalty due to inadequate product availability and service support. This study uses a quantitative method with the Structural Equation Modeling (SEM-PLS) approach to analyze the relationship between variables. Data was collected through a survey to customers of PT. Tirta Sakti Mandiri, including hotels, villas, cafes, and restaurants in Bali. The results of the study show that product diversity and service quality have a positive and significant influence on customer satisfaction, which in turn increases customer loyalty. Customer satisfaction serves as a mediating variable in the relationship between product diversity and service quality to customer loyalty. This study provides managerial implications for PT. Tirta Sakti Mandiri to increase product diversity and service quality to maintain customer loyalty. With the right strategy, companies can build a sustainable competitive advantage.